Sizing and simulation of a photovoltaic installation at the Al-Hoceima desalination plant - Boudraham Salima; Alsayer Ibrahim; Mabrouki Jamal; Aitoujallal Ilham; Abrouki Younes (Desalination and Water Treatment)
One of the major challenges in Morocco is the high energy consumption of desalination plants, coupled with the growing concern over climate change. This has driven the country to explore more sustainable solutions, such as the use of renewable energy, particularly solar power. In this context, we designed a photovoltaic system using PVsyst software to supply the Al-Hoceima seawater desalination plant, with a specific focus on the reverse osmosis unit, as it is the most energy-intensive part of the facility. This paper presents the total energy consumption of the Al-Hoceima desalination plant, the sizing of the PV installation, the peak power capacity used, and a simulation of normalized production and performance ratio, along with the system's energy losses. Finally, an economic and environmental analysis is conducted, detailing the payback period (5,59 years) and the greenhouse gas emissions (GHG) avoided by the system (1830,25 ton/year). The results of this study show that, after installing the photovoltaic system, we achieved an approximate reduction of 10 % in the total energy consumption of the Al-Hoceima desalination plant.